The parasitoid Psyllaephagus blastopsyllae (Hymenoptera: Encyrtidae), as potential control of the eucalypt psyllid Blastopsylla occidentalis (Hemiptera: Psylloidea), in Brazil. - QUEIROZ, D. L. de (2019)
Edição especial dos resumos do IUFRO World Congress, 25., 2019, Curitiba.